GPER and ER: Estrogen Receptors with Distinct Biological Roles in Breast Cancer - J. Filardo, Edward (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
Comparative clinical studies indicate that blockade of estrogen biosynthesis by the use of aromatase inhibitors may have benefit over estrogen receptor (ER) antagonism as a strategy for treating breast cancer. One plausible explanation for this idea is that more than one type of estrogen receptor may promote the biological effects of estrogen. Recent findings that G-protein-coupled receptor-30, (GPR30/GPER) promotes specific estrogen binding and manifests plasma membrane-initiated signaling events suggests that this previously unappreciated receptor may have importance in breast cancer, a concept further supported by the observation that GPER expression is linked to disease progression in cancers that arise from breast, ovary and endometrium. In breast cancer cells, estrogen action via GPER coordinates two cellular activities that have important implications for disease progression, integrin α5β1-dependent fibrillogenesis and release of plasma membrane tethered HB-EGF. GPER has further potential significance in breast cancer in that it acts independently of nuclear steroid hormone receptors, ERα and ERβ, and ER antagonists function as GPER agonists. In support of the idea that GPER may have independent influence from ER in breast cancer, these receptors have been reported to exhibit distinct patterns of association with clinicopathological parameters of disease progression. This review article evaluates this concept and outlines a model by which GPER and ER may act independently to drive breast cancer progression.
Keywords: G-protein-coupled estrogen receptor (GPER)